Recurrent cystic hygroma in adult: A case report - Amar Varshney,; Rajesh Gangavatiker, (Indian Journal of Case Reports, 2021)
Cystic hygroma or cystic lymphangioma is a congenital malformation of the lymphatic system that manifests itself as a soft, benign, and painless mass. It is widely accepted that they arise from the remnants of embryonic lymphatic tissue which retains the potential for proliferation. The majority of cases (80–90%) are diagnosed under the age of 2 and the condition is rare in adulthood. Recurrent cystic hygroma is a known entity and can result from inadequate excision or specific tumor characteristics. We present a case of recurrent cervical cystic hygroma in a 30-year-old female. The patient had undergone excision earlier for a similar type of swelling. She underwent excision and based on histopathology was diagnosed as recurrent cystic hygroma.